The Role of Organizational Commitment as A Mediator on The Influence of Motivation and Training on Employee Performance (Study on the Mataram Class A Search and Rescue Office) - I Wayan Suwena; Ida Ketut Kusumawijaya; Ni Ketut Dewi Irwanti (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the effect of motivation and training on employee performance, with organizational commitment as a mediating variable, at the Mataram Class A Search and Rescue Office. The study employs a quantitative approach. This study uses a saturated sampling technique, which involves selecting the entire population as the research sample. Therefore, the sample size used in this study is 115 employees. Data collection was conducted through questionnaires, observations, and documentation. Data analysis utilized path analysis and the Sobel test to examine the mediating role of organizational commitment. The results indicate that motivation has a positive and significant effect on organizational commitment; training has a positive and significant effect on organizational commitment; motivation has a positive and significant effect on employee performance; training has a positive and significant effect on employee performance; and organizational commitment has a positive and significant effect on employee performance. Furthermore, organizational commitment was found to mediate the effect of motivation on employee performance and to mediate the effect of training on employee performance. These findings suggest that enhancing motivation and training, supported by strong organizational commitment, can optimally improve employee performance at the Class A Search and Rescue Office in Mataram. The implications of this study highlight the importance of boosting motivation through the fulfillment of work needs, the provision of rewards, and opportunities for self-development, as well as the implementation of continuous training programs to strengthen organizational commitment and enhance employee performance.